Ayurveda Literary Research Study on Some Important Aspects of Srotas - Chouhan, Pradeep Kumar (Journal of Drug Delivery and Therapeutics, 2018)
The ancient medical science of India; Ayurveda considered Srotas as an important structural and functions entity of human body. The Hira, Antreshu, Gavinyau, Dhamani, Srotyah, Panth, Khani, Srawanti, Nadi and Dwar are considered as Srotas or they together form Srotas. Akashaa Mahabhut is mainly involves in the constitution of Srotas. Srotas play significant role in the circulation and transportation of various materials. Different studies have been conducted on Srotas, but still there is more to explore in this regards; considering this fact present investigation was planned to conduct more deep study related to ayurveda perspective of Srotas. The article presented critical study of Srotas with special reference to microcirculation in a view to explore all dimensions of micro channels. The study described various concepts related to nature, structure, functions and development of the Srotas.Keywords: Ayurveda, Srotas, micro channels, transportation.